New enantioselective synthesis of antiobesity drug lorcaserin - Ghotekar, Ganesh S.; More, Devidas A.; Nalla, Viswanadh; Muthukrishnan, M. (New Journal of Chemistry, 2019)
A simple and efficient enantioselective synthesis of anti-obesity drug lorcaerin starting from easily accessible 3-chlorostyrene oxide has been described for the first time employing hydrolytic kinetic resolution as a source of chirality. The protocol might also be useful in the synthesis of structural variants of lorcaserin.